THE USE OF VISUAL MEDIA AS A SOURCE FOR DEMOCRATIC LEARNING IN CIVICS EDUCATION IN ELEMENTARY SCHOOLS IN BUNTA SUBDISTRICT BANGGAI REGENCY - Sutoyo Sugito; Udin Hamim; Muchtar Ahmad (SOSIOEDUKASI, 2026)
This study aims to analyze the use of visual media as a learning resource in Civic Education (PPKn) instruction in elementary schools and to examine its implications for learning interaction patterns and student engagement in fostering democratic learning. This study employs a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation at five elementary schools in Bunta Subdistrict. Informants included school principals, teachers, and students. Data analysis utilized the Miles, Huberman, and Saldaña interactive model with source triangulation and. The results indicate that visual media have been consistently used and are effective in enhancing students’ attention and initial understanding. However, their utilization remains instrumental, serving primarily as a tool for conveying information. Learning interaction patterns remain teacher-dominated, so student engagement has not yet evolved into active, dialogic, and reflective participation in Civic Education (PPKn) learning.The novelty of this study lies in the reconstruction of the role of visual media as a source of democratic learning, not merely as a visual aid. This study develops the perspective that visual media can function as a catalyst for interaction, reflection on values, and the formation of students’ civic experiences in Civic Education (PPKn) learning in elementary schools